Antibody to oxidized low-density lipoprotein inhibits THP1 cells from apoptosis by suppressing NF-κB pathway activation - Dai, Rui; Dong, Jing; Li, Weijuan; Zhou, Yi; Zhou, Wei; Zhou, Wenping; Chen, Manhua (Cardiovascular Diagnosis and Therapy; Vol 9, No 4 (August 28, 2019): Cardiovascular Diagnosis and Therapy, 2019)
Background: This study aimed to investigate whether the oxidized low-density lipoprotein (Ox-LDL) antibody is able to inhibit THP1 cell apoptosis by suppressing NF-κB pathway. Methods: THP1 cells were induced to macrophages with phorbol 12-myristate 13-acetate (PMA). Macrophages were divided into control group, Ox-LDL group and antibody group, cells in which were treated with phosphate buffered saline (PBS), Ox-LDL (50 mg/mL), Ox-LDL (50 μg/mL) plus Ox-LDL antibody (100 mg/L), respectively, for 24 h. The apoptosis rate was determined by inverted microscopy and ow cytometry. The protein and mRNA expression of NF-κB (P65), caspase-3 and BCL2 was detected by Western blotting and reverse transcription polymerase chain reaction (RT-PCR), respectively. Results: The apoptosis rate reduced signi cantly in antibody group as compared to Ox-LDL and control groups (P